Strategies for Improving the Economy Based On Micro, Small and Medium Enterprises in the Wong Kito Palembang Gallery (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aims to determine and analyze the improvement of the economy based on Micro, Small and Medium Enterprises (MSMEs) at Wong Kito Gallery Palembang. Wong Kito Gallery Palembang initiated a program to use horticultural waste as a dye in making natural batik. This program itself is a flagship Corporate Social Responsibility (CSR) program of PT PLN Indonesia Power Keramasan Generating Unit called Pesona (Plant based Recycling on Ecoprint Innovation) Sriwijaya. Pesona Sriwijaya is one of the flagship CSR programs of PT PLN Indonesia Power Keramasan Generating Unit which raises the issue of empowering women and vulnerable groups. Batik CINDO or Clean Batik is one of the new products from Pesona Sriwijaya. Clean batik is the result of a natural batik making process and does not use chemicals. The stage of making batik from the initial stage to the final stage which usually uses several types of chemicals is then changed to natural materials. The goal is that Pesona Sriwijaya becomes a program that continues to innovate to produce environmentally friendly products.